Why Hungary? Why Kaposvár? Foreign students’ motivations, why they study in our country, at MATE Kaposvári Campus - Szilvási-Bódis, Zsuzsanna (SZAKNYELV ÉS SZAKFORDÍTÁS, 2023)
First, the study reviews the opportunities for foreign students to study in Hungarian higher education. It shows in what form and under what framework they can study in higher education institutions in our country. It also discusses which countries most people come to Hungarian universities from, and which majors are the most popular. After that, the study presents the results of a survey conducted among foreign students of MATE Kaposvári Campus. The programme has been operating successfully in our institution for several years, and every year students come to our campus from abroad. Looking back a few years, you will see why they chose our institution, and what their main motivations were for choosing it.